Rancang Bangun Aplikasi Pemesanan Material Bangunan Berbasis Mobile - Teten Dwi Rahmi Kiflinda; Yuhefizar; Rita Afyenni (Prosiding SISFOTEK, 2021)
The Telaten Karya application is a medium for ordering tools and building materials at the Telaten Karya shop. Through this application, customers can order building materials anywhere and anytime, then make it easier for customers to get the latest product data updates. The development of this ordering application uses the Waterfall method, a storage system with a MySQL database, and uses the Application Programming Interface (API) as a communication medium between the system as a server and the android application as a client. After implementing this application, the promotion and customer service process becomes easier.